Prenatal Diagnosis and Fetal Outcomes of Cystic Hygroma: Experience of a Tertiary Hospital - Betul Yakistiran; Doruk Cevdi Katlan; Tuncay Yuce; Feride Soylemez (Gynecology Obstetrics & Reproductive Medicine, 2019)
Objective: Cystic hygromas of nuchal origin are reported to be associated with fetal aneuploidy and structural anomalies in 50-80% of the cases. We aimed to report our experience on cystic hygromas via 18 cases.